PENGARUH ORGANISASI KEMAHASISWAAN TERHADAP PEMBENTUKAN KARAKTER KEPEMIMPINAN MAHASISWA DI STAI MA’HAD ALY AL-HIKAM MALANG - Halimatus Sa’diyah; Siti Mutholingah (STAI Ma'had Aly Al-Hikam Malang, 2025)
In order to preserve justice and the truth, student organizations and movements support students in expressing their goals. Along with developing their interests, skills, and innovations, students can also become more perceptive and logical. The purpose of this study is to ascertain whether student groups at the Islamic College